PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Putra, Robby Hartono; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is conducted in order to obtain empirical evidence about the influence of corporate governance tothe financial performance. The population is all banking companies which are listed in Indonesia Stock Exchangein 2013-2015 periods. Based on the result of the purposive sampling method, 16 companies have been selected assamples. The analysis instruments are multiple regressions statistics in which the dependent variable is thefinancial performance (return on assets), and the independent variables are board of directors, audit committee,managerial ownership, institutional ownership. The result of the model feasibility research indicates thatcorporate governance which is proxy by board of directors, audit committee, managerial ownership, institutionalownership give positive influence to the financial performance of banking companies. The result of partial test ort test shows that the board of directors, audit committee, managerial ownership give positive influence to thefinancial performance of banking companies, Meanwhile the institutional ownership gives negative influence tothe financial performance of banking companies.Keywords: Board of directors, audit committee, managerial ownership, institutional ownership, financialperformance.